Overview of criminal cases concerning illegal withdrawal of wild falcons and related prosecutions in Russia and neighboring countries - Elvira G. Nikolenko (Пернатые хищники и их охрана, 2018)
This article was prepared according on the analysis of the situation with the poaching and smuggling of falcons (Gyrfalcon Falco rusticolus, Saker Falcon F. cherrug and Peregrine Falcon F. peregrinus) in Russia and near abroad countries in 2016–2017. The number of falcon-related arrests is steadily growing: 6.3 arrests per year in 1996-2005, 10.3 in 2006-5015 and 15.0 in 2016-2017. About half of all arrests took place in Kamchatka peninsula where governmental nature-protection authority works in collaboration with Federal Security Service and Border Control Service that leads to significant decrease of the number of illegally caught Gyrfalcons in 2017. One-third of all cases occurred in Siberia. The proportion of identified crimes in Moscow and St. Petersburg is relatively low – only 0.83 cases per year on average. In the last 12 year, the number of falcon-related arrests in the neighboring countries increased – from 2.6 crime cases per year in average in 2006-2015 to 7.5 crime cases per year in 2016-2016. The mean number of falcons annually withdrawal illegally from the nature increased 1.64 times during the last 2 years compared with the previous decade: from 76.3 individuals per year to 125.5 ind/year. This increase was mainly due to enhanced poaching in the Middle Asia where this index grew from 17.9 to 39 individuals per year. From 2014 to 2017, 36 peoples were convicted for a crime – 16 were sentenced to a colony and 20 got a suspended sentence. The strictest sentences were passed for smuggling (clause 226.1 of the criminal code of Russia) – from 2 years and 3 months to 6 years of the suspended sentence and from 2 years and 3 months to 7.5 years of a colony (22 convicted). On the other clause – illegal hunting, keeping and transportation of falcons (clause 258.1) 17 peoples were convinced – two of them were convinced to a colony, the rest got suspended sentence from 2 to 4 years.